Blueprint : Green Hiking Nature Jacket / Hadi Zami Hasnor - Hasnor, Hadi Zami (2020)
Our business will introduce a new product namely GHN Jacket which is a product that is creates for hikers that always go hiking. This product highlights the importance of creativity and innovation to the entrepreneurs in industry. If we survey at the hiking shop or accessories shop, sometimes they do not have innovation for the existing jacket. The latest for the innovation just the material of the jacket which is waterproof and windproof. Our company found something that to be made. For instance, the company take this problem seriously to solve problem of hikers with technology. This is also because of the trend that spread nowadays which technology plays the important roles in this era. Our target markets for this product are hikers, traveller, or sport team community the accessories shops